DYPHEMIA IN DIDONG JALU ARITA MUDE AND BIAK CACAK: DISFEMIA DALAM DIDONG JALU ARITA MUDE DAN BIAK CACAK - Sediken Tara Munthe; Azman Ismail; Yusri Yusuf; Denny Iskandar; Ramli Ramli (Jurnal Kata, 2022)
This study aims to describe the type, function, and linguistic form of dysphemia in Didong Jalu Arita Mude and Biak Cacak. The method used is a descriptive method with a qualitative approach. The technique used is listening, note-taking, and interview techniques. The data of this study are expressions containing dysphemia taken from the video of the performance of Didong Jalu Arita Mude with Biak Cacak. In data collection, 2 respondents participated in the interview and were justified by 2 other respondents. The results showed that in the Didong Jalu poem there were various types, functions and linguistic forms of dysphemia, namely; in the expressions mulaho, naru delahe, lenge mubute beloh gere mera, muperot, silent monkey, etc.